Anaphylaktische Reaktionen auf Impfstoffe: Hühnereiweißallergie und Influenza-H1N1-Impfung = Anaphylactic reactions to vaccines : hicken egg allergy and the influenza H1N1 vaccination - Klimek, Ludger; Thorn, Carsten Volker; Cazan, Dorotheea; Hörmann, Karl (HNO, 2017)
Background: Allergic reactions to influenza vaccinations are a well-known phenomenon; however, only a few published statistics give information on the risks. Patients with a chicken egg allergy must be particularly carefully handled during an influenza epidemic where vaccines produced using embryonated chicken eggs are primarily employed. Methods: A selective literature review and analysis of the problem of allergic reactions to vaccinations was performed. Results: The two most common relative contraindications among patients to be vaccinated are the presence of an egg allergy and a previous anaphylactic reaction to vaccination. These patients have a significantly increased risk of sustaining an adverse reaction. These high-risk patients should therefore only be vaccinated on the basis of thorough assessment of medical history, and then only with caution. The emergency routine must include sufficient precautionary measures, in case an anaphylactic reaction occurs. Conclusion: Current guidelines for the treatment of anaphylactic reactions are to be observed. Immediate treatment of the first symptoms of an anaphylactic reaction - i.v. administration of adrenalin, antihistamines, cortisone, and in some cases betamimetics - can usually prevent anaphylactic shock. Alternatively, a graded vaccination (“split protocol”) and overnight surveillance can be considered in this group of patients.
Gesehen am 08.11.2018